Correlations between the peptide profile and the antioxidant and the ACE inhibitory activities of whey protein concentrate hydrolysates - Morais, H. A.; Silvestre, M. P. C.; Gonçalves, J. H. T.; Silva, M. R.; Monteiro, M. R. P. (Scientific Electronic Archives, 2018)
The peptide profile, the angiotensin converting enzyme-inhibitory activity (ACE-IA) and the antioxidant property are important characteristics of protein hydrolysates and this was the first time the correlation among these parameters was investigated. Twenty-four hydrolysates from whey protein concentrate were prepared using four enzymes. With respect to the antioxidant activity, when using the B. licheniformis protease, a positive and significant correlation of strong intensity was observed with the contents of di- and tripeptides and medium peptides. Also, a negative and significant correlation of strong intensity was observed with the large peptide content. For the A. sojae protease and pancreatin, a positive and significant correlation of strong intensity was observed with the contents of di-and tripeptides. For the A. sojae protease, a negative and significant correlation of strong intensity was observed with the large peptide content. Concerning the ACE-IA, for the B. licheniformis and A. sojae proteases and pancreatin, a positive and significant correlation of strong intensity was observed with the contents of di-and tripeptides and medium peptides. For the A. sojae protease and pancreatin, this same kind of correlation was observed with the free amino acid content. For the B. licheniformis, A. sojae and A. oryzae proteases and pancreatin, a negative and significant correlation of strong intensity was observed with the large peptide content.